Structural and electronic properties of β-CuPc: First principles study - Nuleg, Witoon; Thanomngam, Pitiporn; Phacheerak, Kanoknan Sarasamak (My University, 2016)
Structural and electronic properties of CuPc in β structure (β-CuPc) were investigated by first principles calculations. The generalized gradient approximation (GGA) was used to describe the exchange-correlation with the projector-augmented wave (PAW) method. Under ambient pressure, the calculated structural parameters were calculated and found to be in good agreement with other experimental and theoretical values. The calculated direct band gap was found to be 0.683 eV. The results of electronic properties under various pressures were presented. To investigate the properties under pressure, β-CuPc was calculated at several reduced volumes. It was found that the energy gap decreases when the pressure increases. The behaviors of electronic properties under pressure were also discussed.
Keywords: Copper phthalocyanine; Electronic structure properties; First principles calculations; Pressure